Policy Reform Towards Waste Management in Pontianak Municipality, West Kalimantan Indonesia (A SWOT Analysis and Lessons Learned from Kyoto City) - Rahman, Syaiful; Supriyono, Bambang; Hariswanto, Alfi; Koyama, Masahisa (Jurnal Ilmiah Administrasi Publik, 2020)
This study aims to describe the current state of the implementation of wasteÂ management as part of public service provision in Pontianak Municipality, West Kalimantan, Indonesia. For this purpose, this study employed a qualitative descriptive approach by applying SWOT analysis accompanied by lessons learned from Japan. The findings indicated that there has been an increase in waste transportation services year by year and that the waste management carried out by Pontianak Municipality still primarily relies on landfill. Waste reduction efforts through 3R programs such as integrated waste treatment plant and waste bank have not shown significant results in reducing the generation of waste. Using SWOT analysis, several factors that affect the performance of waste management in Pontianak Municipality were identified. By considering those influencing factors and learning from best practices executed by Kyoto City, this study suggests that the government needs to develop an integrated waste management based on priority scale with measurable and realistic objectives, particularly those related to reduction and recycling activities as well as stakeholderâ€˜s engagement.